2021
DOI: 10.1002/ange.202110619
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Arylation of P4 and PH3: Reaction Development Through Mechanistic Insight

Abstract: Detailed 31 P{ 1 H} NMR spectroscopic investigations provided eeper insight into the complex, multi-step mechanisms involved in the recently reported photocatalytic arylation of white phosphorus (P 4 ). Specifically,t hese studies have identified anumber of previously unrecognized side products, which arise from an unexpected non-innocent behavior of the commonly employed terminal reductant Et 3 N. The different rate of formation of these products explains discrepancies in the performance of the two most effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…These experiments visualized the evolution and consumption of primary, secondary and tertiary monophosphine intermediates, and identified traces of Ph 4 P 2 , benzene and Et 2 NH as minor side‐products (Figure 11). A follow‐up study using an organic photocatalyst (3DAFIPN) revealed numerous additional intermediates and side‐products that are derived from a non‐innocent behavior of Et 3 N [51] . Of specific interest was the identification of PH 3 , which prompted the authors to develop an alternative strategy that can directly convert this industrial P 1 precursor to several Ar 3 P and Ar 4 P + products using a similar photocatalytic protocol.…”
Section: Mechanistic Insights Gained Through Reaction Monitoringmentioning
confidence: 99%
“…These experiments visualized the evolution and consumption of primary, secondary and tertiary monophosphine intermediates, and identified traces of Ph 4 P 2 , benzene and Et 2 NH as minor side‐products (Figure 11). A follow‐up study using an organic photocatalyst (3DAFIPN) revealed numerous additional intermediates and side‐products that are derived from a non‐innocent behavior of Et 3 N [51] . Of specific interest was the identification of PH 3 , which prompted the authors to develop an alternative strategy that can directly convert this industrial P 1 precursor to several Ar 3 P and Ar 4 P + products using a similar photocatalytic protocol.…”
Section: Mechanistic Insights Gained Through Reaction Monitoringmentioning
confidence: 99%
“…The compound 2,4,6-tris(diphenylamino)-5-fluoroisophthalonitrile (3DPAFIPN) has been increasingly utilized in various synthetic procedures that are activated by visible light. Examples of such protocols include intramolecular cyclizations 11 , 12 as well as the formation of C–C 13 , 14 , N–C 15 , and P–C 16 bonds 5 .…”
Section: Introductionmentioning
confidence: 99%